Reputation: 128
I have a doubt, I have to do a tail recursion for this pow function:
pow(_, 0) -> 1;
pow(N, X) when X > 0 -> N * pow(N, X - 1).
I've read about it, but I do not totally get it, Can somebody explain me how to this function in tail recursion?
Upvotes: 2
Views: 85
Reputation: 6834
Basically in a tail recursion you need a another parameter that act as an accumulator.
%% So the first step is to convert the pow function to the pow_tail function, and initialize the accumulator to the default value.
pow(N, X) -> pow_tail(N, X, 1);
%% Defined the base case for the pow_tail, to return the accumulator
pow_tail(_, 0, ACC) -> ACC;
%% Write the pow_tail function and store the result in the accumulator
pow_tail(N, X, ACC) when X > 0 -> pow_tail(N, X-1, ACC * N);
Hope this gives you an idea how it can be done.
Upvotes: 6